Managing failure: Sir Peter Brian Medawar’s transplantation research - Park, Hyung Wook (2018)
Sir Peter Medawar experimentally demonstrated immunological tolerance through his tissue transplantation experiment in the early and mid-1950s. He made a central contribution to modern biomedicine by showing that genetically distinct cells introduced into a body during its foetal phase could not only be permanently tolerated but also make the host accept any subsequent skin grafts from the original cell donors. However, this discovery had only a limited clinical applicability. None could practise Medawar's method on human foetuses in preparation for their future need for organ or skin transplantation. I analyse this problem by focusing on his management of ‘failures’ during the tissue transplantation experiments. Through statistical, material, theoretical and rhetorical strategies, he managed unsatisfactory findings of his research, including unexpected skin infection, sudden animal death and irregularities in homograft survival times. I argue that these strategies and their inherent ambiguities constituted the course of Medawar's research, enabling him to delineate the temporal dimensions of tolerance and a clinical relevance, which were mutually contradictory. This paper thus illustrates the multiple roles that failures play in scientific research as well as the conflicting outcomes of investigators' efforts to manage them.